Direct ortho Arylation of Anisoles via the Formation of Four-Membered Lithiumcycles/Palladacycles - Xiong, Xiaoyu; Zhu, Ranran; Huang, Lin; Chang, Shuqin; Huang, Jianhui (Synlett, 2017)
We report here our latest discovery on the directed lithiation and palladium-catalyzed arylation of anisoles. During this research, the formation of a four-membered lithiumcycle followed by transmetalation to the corresponding palladacycle has been achieved, which is difficult to be obtained from palladium-catalyzed C–H activation processes. This approach has provided an alternative way of introducing functionalities to arenes such as anisoles, thioanisoles, and anilines. This approach also features an excellent monoselectivity compared with reactions under transition-metal-catalyzed conditions.
Keywords: directed lithiation; lithiumcycle; transmetalation; mono-selectivity; palladium-catalyzed arylation